Associated Factors to Human Papilloma Virus. A study performed in Health Area V, in Cienfuegos, Cuba. - Miryam González González del Pino; Mayrim Hernández González; Adys Castro Barberena (Medisur)
Background: Human Papilloma Virus has been considered as the precursor of flat lesions in the cervical epithelium which develops Cervix uterine cancer. Objectives: to analyze risk factors associated to infections due to human papilloma virus. Method: An ambispective, descriptive study was carried out from January 2003 to January 2004, taking 60 patients whose Papanicolaou smears were abnormal. All these patients belonged to health area V, in Cienfuegos, Cuba. A guide for interview with different variables was used. Results: infected predominant ages were from 30 to 39 years old. 55% of the patients are married women or with stable sexual relationships. 6 patients comprised between 40 to 59 years old were observed with association to intra epithelium cervix neoplasias. For a 10 % of them, they have had from 3 to 12 sexual partners. The starting age to have sexual intercourse is from 15 to 19 years old. 75 % of the patients are smokers. Conclusions: results coincide with the medical literature reviewed regarding risk factors and its important relationship with NIC and so the cervicouterine cancer genesis.